2015
DOI: 10.1007/s00439-015-1583-0
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic maternal ancestry in the Great Lakes region of East Africa

Abstract: The Great Lakes lie within a region of East Africa with very high human genetic diversity, home of many ethno-linguistic groups usually assumed to be the product of a small number of major dispersals. However, our knowledge of these dispersals relies primarily on the inferences of historical linguistics and oral traditions, with attempts to match up the archaeological evidence where possible. This is an obvious area to which archaeogenetics can contribute, yet Uganda, at the heart of these developments, has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Although the frequency of these lineages throughout the various aboriginal groups was never greater than 50 % (except in the Ami, with 56 %), it appears therefore that the admixture that generated the current maternal gene structure of Taiwanese tribes took place progressively after the “out-of-Taiwan” expansion. At the time the “out-of-Taiwan” dispersal occurred, the expanding population seems to have remained distinct, with a full South Chinese ancestry (similar to what also seems to have happened to a considerable degree in Central Europe (Haak et al 2010 ) and in the Great Lakes region during the Bantu expansion (Gomes et al 2015 ; Silva et al 2015 ). Whether the subsequent admixture with autochthonous groups (and, presumably, the assimilation of the language) was rapid or protracted we cannot assess from contemporary data alone, in the absence of ancient DNA evidence.…”
Section: Discussionmentioning
confidence: 89%
“…Although the frequency of these lineages throughout the various aboriginal groups was never greater than 50 % (except in the Ami, with 56 %), it appears therefore that the admixture that generated the current maternal gene structure of Taiwanese tribes took place progressively after the “out-of-Taiwan” expansion. At the time the “out-of-Taiwan” dispersal occurred, the expanding population seems to have remained distinct, with a full South Chinese ancestry (similar to what also seems to have happened to a considerable degree in Central Europe (Haak et al 2010 ) and in the Great Lakes region during the Bantu expansion (Gomes et al 2015 ; Silva et al 2015 ). Whether the subsequent admixture with autochthonous groups (and, presumably, the assimilation of the language) was rapid or protracted we cannot assess from contemporary data alone, in the absence of ancient DNA evidence.…”
Section: Discussionmentioning
confidence: 89%
“…More generally, the Horn of Africa is exceptional in harbouring very high mtDNA haplogroup diversity 4 , and populations in the Horn have significant non-autochthonous African ancestry across the genome 5 6 7 8 9 10 . Recent studies of complete human genomes have concluded that this 30–50% of non-African legacy in Cushitic- and Semitic-speaking populations is the result of admixture from Arabia beginning ~3,000 years ago (3 ka) 11 12 , at a time when common cultural features developed across the Horn and southern Arabia 13 , suggesting a link with the origin of the Ethiosemitic languages 14 .…”
mentioning
confidence: 99%
“…The data also point to important sex-biased dispersals between populations. These evident gene replacements in Africa have been mainly attributed to recent geographic range expansions of pastoralist and agriculturalist populations from eastern and western Africa at the expense of the hunter-gatherers inhabitants of the Central Africa rainforest [108110], eastern African forested areas around the Great Lakes [111114], and the semi-desert open spaces of South Africa [115118]. Under our hypothesis of an early return to Africa from Eurasia of basic mtDNA L3 and Y-chromosome E lineages, and their expansion around 70 kya first into East and later into West Africa, those lineage replacements must have begun very early.…”
Section: Resultsmentioning
confidence: 99%
“…The same “centre-of-gravity” argument was used by other authors to suggest a Central African origin [126]. It is worth mentioning that while ancestral southern African Khoesan-speaking population still maintain high frequencies of primitive L0d and k lineages [94, 106, 127, 128], and that in the hunter-gatherer populations of central-western Africa the L1c haplogroup is dominant [108, 109], L5 in eastern Africa has today only a marginal presence [114, 129], most probably due to its displacement produced by more recent waves of better adapted incomers. The presence of L5 in southern Africa and eastern Mbuti pygmies [70, 109, 118, 127] is the result of later migrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation